Manajemen Stres Peserta Didik pada Sistem Full Day School dengan Program Tahfidz - Hidayah, Titi Nur; lestari, sri; Sofiyatun; Pradana, Akhmad Aji (STIT Fatahillah, 2026)
This study aims to analyze students’ stress management within a full day school system integrated with a Qur’anic memorization (tahfidz) program. The research employed a descriptive qualitative approach involving tahfidz teachers and firstgrade students in an Islamic elementary school implementing a full day school model. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques with source and method triangulation to ensure validity. The findings indicate that the implementation of a full day school combined with a tahfidz program does not automatically lead to severe academic stress. Stress is influenced by students’ cognitive appraisal, intrinsic motivation, self-regulation skills, and social support from teachers and parents. The tahfidz program functions not only as a cognitive activity but also as a form of religious coping that strengthens emotional regulation, resilience, and spiritual meaning-making. Supportive teacher guidance, parental involvement, structured learning management, and strong spiritual motivation significantly contribute to adaptivestress management. Therefore, when properly managed, the integration of a full day school system with a tahfidz program can serve as a holistic educational model that balances academic achievement, character development, and students’ psychological well-being.